LncRNA ZNF593-AS Alleviates Contractile Dysfunction in Dilated Cardiomyopathy. Issue 11 (8th February 2021) - Fan, Jiahui; Li, Huaping; Xie, Rong; Zhang, Xudong; Nie, Xiang; Shi, Xiaolu; Zhan, Jiabing; Yin, Zhongwei; Zhao, Yanru; Dai, Beibei; Yuan, Shuai; Wen, Zheng; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Previously, we identified the human cardiac long noncoding RNAs (lncRNAs) profile in patients with dilated cardiomyopathy (DCM), among which ZNF593-AS, also named as RP11-96L14.7 and ENST00000448923.2, showed good conservation among species. Objective: We aim to elucidate the mechanism underlying lncRNA in DCM and DCM that lead to heart failure, which might provide new insights into the mechanisms of DCM and possible treatment strategies in the future. Methods and Results: LncRNA expression was measured by real-time polymerase chain reaction and in situ hybridization assays. Coding potential was verified by bioinformatic and biologic assays. Recombinant adeno-associated virus with cardiac-specific promoter was used to deliver lncRNA in vivo, while cardiac structure and functions were assessed by echocardiography and catheter. Sarcomere shortening, calcium imaging, gene expression profiling, and pull-down assays were performed to investigate the underlying mechanisms. ZNF593-AS, which mainly localized in the cytoplasm of cardiomyocytes, was robustly decreased in the failing heart of patients with DCM, as well as in phenylephrine-treated human cardiomyocytes. Overexpression of mmu-ZNF593-AS significantly improved transverse aortic constriction-induced cardiac dysfunction in mice. Moreover, ZNF593-AS overexpression restored the aberrant Ca 2+ handling and contractility of cardiomyocytes from transverse aortic constriction-treated mice. Furthermore, we found that ZNF593-AS acted as a guide RNA scaffold and recruited HNRNPC (heterogeneous nuclear ribonucleoprotein C [C1/C2]) to RYR2 (ryanodine receptor type 2) mRNA, which, in turn, facilitated RYR2 mRNA stability, contributed to the improvement of cardiac Ca 2+ handling and contractile function in DCM. Conclusions: Our findings suggested that lncRNA-based therapeutics may protect against DCM.